Strengthening Productivity: Role Analysis of Workload, Compensation, Work Environment, and Work Discipline - Yosep Hardian Devates; Prayekti; Didik Subiyanto (Relevance: Journal of Management and Business, 2024)
Examine the relationship between workload, compensation, and work environment on work productivity, taking into account the role of work discipline as a mediator. This study applies quantitative approaches and survey methods to assess the impact of workload, compensation, and work environment on work discipline and work productivity. Likert questionnaires 1 to 5 were used as a comprehensive research instrument. Data was collected from 147 respondents at various levels within several companies. Data analysis uses Structural Equation Models (SEM) with the help of AMOS software to identify relationships between independent and bound variables.The results of the analysis showed that the relationship between workload and work discipline was not significantly confirmed. Likewise, the relationship between compensation and work discipline was also not significantly confirmed.  However, there is significant confirmation that the work environment has a positive effect on work discipline.  In addition, there is significant confirmation that work discipline has a positive effect on work productivity. The results of the analysis suggest that a focus on workload management and compensation may not be significant in improving employee discipline and productivity. The implication is that it needs to be focused on creating a supportive work environment, as well as paying attention to and strengthening work discipline in human resource management strategies to increase overall productivity.